Pengaruh Green Perceived Knowledge dan Environmental Concern Terhadap Eco-Friendly Behavior - Nadya Novita; Nurdin Nurdin; Rahmah Dianti Putri (FKIP Universitas Lampung, 2020)
The purpose of this research is to know effect green perceived knowledge and environmental concern in Economic Education Students Lampung University 2019. This research used descriptive verification with ex post facto and survey approach. Population of this research is Economic Education Students Lampung University 2019 by the amount of 67 students and sample by the amount of 67 students. Collecting the data is done by observation, interview, documentation and questionnaire. The analysis technique used simple linear regression and multiple linear regression. Based on the results of data analysis, it is known that eco-friendly behavior is influenced by green perceived knowledge and environmental concern of 67,7% and the remaining 32,3% is influenced